ОСОБЕННОСТИ ГРАЖДАНСКО-ПРАВОВОЙ ЗАЩИТЫ ПРАВ И ЗАКОННЫХ ИНТЕРЕСОВ СУБЪЕКТОВ ПРЕДПРИНИМАТЕЛЬСТВА - Татар, Ольга Владимировна (SUPREMAȚIA DREPTULUI, 2017)
In the article the author generalizes and systematizes the features of civil-law protection of the rights and legitimate interests of subjects of entrepreneurship in the modern market economy of the Republic of Moldova and recommendations on improving the legislative framework; drawn to the attention of the state to businesses in need of its protection in case of violation of these rights from the outside.